폐 이차전지 리사이클링을 위한 건식공정 생성물 분석 - 김진한(Jinhan Kim); 김용철(Yongcheol Kim); 오승교(Seung Kyo Oh); 전종기(Jong-Ki Jeon) (Clean Technology, 27(2), 2021)
The purpose of this study is to recover valuable metals from spent batteries using a dry process. We focused on the effect of the smelting temperature on the composition of recovered solid and liquid products and collected gaseous products. After removal of the cover, the spent battery was left in NaCl solution and discharged. Then, the spent battery was made into a powder form through a crushing process. The smelting of the spent battery was performed in a tubular electric furnace in an oxygen atmosphere. For spent lithium-ion batteries, the recovery yield of the solid product was 80.1 wt% at a reaction temperature of 850 ℃, and the final product had 27.2 wt% of cobalt as well as other metals such as lithium, copper, and aluminum. Spent nickel-hydrogen batteries had a recovery yield of 99.2 wt% at a reaction temperature of 850 ℃ with about 37.6 wt% of nickel and other metals including iron. For spent nickel-cadmium batteries, the yield decreased to 65.4 wt% because of evaporation with increasing temperature. At 1050 ℃, the recovered metals were nickel (41 wt%) and cadmium (12.9 wt%). Benzene and toluene, which were not detected with the other secondary waste batteries, were detected in the gaseous product. The results of this study can be used as basic data for future research on the dry recycling process of spent secondary batteries. 본 연구의 목적은 건식 공정을 통해 폐전지에서 금속을 회수하는 것이다. 특히, 열처리 온도를 변수로 하여 공정 중에 발생되는 액상 및 기상상태의 생성물과 공정 후에 회수되는 고상상태의 생성물에 대하여 정성 및 정량적으로 분석하여 비교하였다. 폐전지의 커버를 제거한 후, NaCl 용액에 존치하여 방전시켰다. 폐전지를 파쇄과정을 통하여 가루형태로 만들어서 산소 분위기의 튜브 전기로에서 폐전지의 용융실험을 수행하였다. 리튬이온 폐전지는 반응온도 850 ℃에서 고체상태 생성물의 회수율은 80.1 wt%이었고, 주성분은 27.2 wt%의 코발트이었으며 그 외 리튬, 구리, 알루미늄 등이 미량 존재하였다. 니켈-수소 폐전지는 반응온도 850 ℃에서 회수율이 99.2 wt%로 건식공정으로부터 손실되는 금속이 거의 없었으며 약 37.6 wt%의 니켈이 주성분이었다. 그 외, 철을 포함하여 여러 금속을 가지고 있다. 니켈-카드뮴 폐전지는 온도가 증가할수록 카드뮴이 기화되면서 회수율이 65.4 wt%까지 낮아진다. 반응온도 1050 ℃에서 회수된 고체상태의 주 금속성분은 41 wt%의 니켈과 12.9 wt%의 카드뮴이었다. 또한 니켈-카드뮴 폐전지는 다른 이차 폐전지로부터 검출되지 않은 벤젠과 톨루엔 성분이 기체상태의 생성물에서 검출되었다. 본 연구 결과는 폐 이차전지의 건식 리사이클링 공정 연구에 기초 자료로서 활용 가능하다.